Chrysanthemum indicum L. ameliorates muscle atrophy by improving glucose tolerance in CT26-induced cancer cachexia - Song, Gahee; Choi, Minji; Park, Woo Yong; Kim, Sang Hee; Jiao, Wenjun; Park, Ja Yeon; Ahn, Kwang Seok; Kwak, Hyun Jeong; Um, Jae-Young (Frontiers in Pharmacology, 2024)
Cancer cachexia is associated with various metabolic mechanisms such as inflammatory response, insulin resistance, and increased muscle proteolysis. However, effective treatment methods have not yet been standardized. Chrysanthemum indicum L. (CI) is a perennial plant belonging to the Asteraceae family, and its flowers have been used for the treatment of headaches, colds, and rhinitis in Asia. This study investigated the effect of CI on cancer cachexia. We subcutaneously injected CT26 colon cancer cells (5 × 105 cells/mouse) into the right flank of BALB/c mice. After 1 week, the mice were orally administered vehicle, CI (100 mg/kg), or Celecoxib (50 mg/kg) for 3 weeks. CI improved loss of body weight and impaired glucose tolerance, but celecoxib did not recover the body weight and glucose intolerance. CI not only improved the decreased myofiber diameters but also inhibited muscle protein degradation factors, MAFbx and MuRF1. CI also increased cellular membrane GLUT4 in CT26 conditioned medium-treated C2C12 myofibers and cancer cachexia-induced mice. Furthermore, we found that linarin, a constituent of CI, was responsible for the improvement of muscle atrophy. Our findings indicate that CI can ameliorate muscle atrophy by improving glucose uptake, suggesting that CI could be a therapeutic agent for cancer cachexia.